Water Contamination from Pesticides in Crop Runoff - Barrett, Olivia (Kansas State University. K-State Libraries, 2022)
When deciding on my research topic, I applied what I had learned in a few of my classes to the real world. Most places in Kansas get their drinking water from local streams and rivers, and it is a big issue if pesticides are flowing into the streams and rivers from crop runoff. In recent years, many places in Northeastern Kansas have had increased rainfall and there has been more runoff from the fields. Most fields are located in flood plains or near creeks and rivers. I thought it would be interesting to see how pesticides from crop runoff affect the local rivers and streams. This is an important topic that does not get discussed very often. I did some background reading to make sure this was the topic that I wanted to focus on, but it was my own family experience that refined my topic.
Kirmser Undergraduate Research Award - Individual Freshman category, honorable mention
Keywords: Pesticides; Drinking Water; Water Contamination; Crop Runoff; Northeaster Kansas; Streams and Rivers